The effects of perspective taking primes on the social tuning of explicit and implicit views toward gender and race - Skorinko, Jeanine Lee McHugh; DiGiovanni, Craig; Rondina, Katherine; Tavares, Amy; Spinney, Jennifer; Kobeissi, Mariam; Lacera, Luisa Perez; Vega, Daniel; Beatty, Paul; John, Melissa-Sue; Doyle, Aidan (Frontiers in Psychology, 2023)
Perspective taking can benefit interpersonal situations by helping communication and decreasing explicit and implicit biases. However, perspective taking can also backfire and highlight differences and increase biases. The current research investigates whether perspective taking influences social tuning, or the alignment of one’s self-views, explicit attitudes, and/or implicit attitudes with those of an interaction partner. Experiments 1-2 examine whether perspective taking with an ostensible interaction partner who endorses gender traditional (or non-traditional) views align their views with this partner. Experiments 3-5 investigate whether perspective taking leads to social tuning for egalitarian racial attitudes, including when the partner’s expectations of the interaction are clear and when the participant learns their ostensible IAT score at the beginning of the session. Across all experiments, perspective takers are more likely to social tune their self-views and explicit attitudes than non-perspective takers. However, social tuning never occurs for implicit attitudes. Neither affiliative motivation towards the interaction partner nor self-presentation influences the results. Thus, while perspective taking leads to social tuning, it does not completely replicate past work as there was only social tuning for self-views and explicit attitudes, not implicit attitudes.